Development of a methodology for teaching RFL using short videos (Eurasian Journal of Philology Science and Education, 2021)
Currently, the growing interest of Chinese students in the study of the Russian language requires the search for new teaching methods that are more effective and meet the needs of modern young people. The article argues that with the development of new media, new video formats are emerging, including short videos. A feature of this video format is its limited time, which leads to a high concentration of information within a single video clip. It is noted that solving the problem of increasing the effectiveness of teaching RFL requires the search for new, more effective teaching methods. One of these teaching methods is the audiovisual method based on the use of short video technology. Using the methods of scientometric analysis and content analysis, the article identifies the advantages of using short videos in RFL lessons, and highlights their main types. The developed methodology for conducting a lesson using short videos was tested in China and it was found that the use of short videos in RFL lessons can improve the effectiveness of lessons. According to the results of the study, the author notes that it is promising to develop a series of short videos with accompanying teaching materials for teaching Chinese students the Russian language, and the content of the assignment and exercises on each topic studied.